Fuzzy logic control of a non-linear structural system against earthquake induced vibration - Guclu, Rahmi; Yazici, Hakan (SAGE PUBLICATIONS LTD, 2007)
In this paper, the problem of active vibration control of multi-degree-of-freedom structures is considered. Fuzzy logic and PID controllers are designed to suppress structural vibrations against earthquakes under the non-linear soil-structure interaction. The advantage of the fuzzy logic approach is the ability to handle the non-linear behavior of the system. Non-linear behavior of the soil is modeled in the dynamics of the structural system with non-linear hysteric restoring forces. The simulated system has fifteen degrees of freedom, which is modeled using spring-mass-damper subsystems. A structural system was simulated against the ground motion of the destructive Kocaeli earthquake (M-w = 7.4) in Turkey on 17 August 1999. At the end of the study the time history of the storey displacements and accelerations, the control voltages and forces, and the frequency responses of both the uncontrolled and the controlled structures are presented. The performance of designed fuzzy logic control is checked using the changing mass parameters of each storey and the results are discussed. These results show that the proposed fuzzy logic controller has great potential in active structural control.
Keywords: fuzzy logic control; PID control; non-linear structure; earthquake induced vibration; SLIDING MODE; MASS-DAMPER; BUILDINGS; SUSPENSION; Acoustics; Engineering; Mechanics